A Study of Mix Design Adopted in RMC: Exploring the Mix Design and Properties of Ready-Mixed Concrete (Journal of Advances and Scholarly Researches in Allied Education, 2018)
While concreting, it is important to select suitable ingredients of concrete and to produce concrete of certain minimum strength and durability. To achieve these points it is required to design a concrete mix. Mix Design can be defined as the process of selecting suitable ingredients of concrete and determining their relative proportion with the object of producing concrete of certain minimum strength and durability as economically as possible. For ready mix concrete plant, it is required to follow up the good concrete mix design. Therefore, in this seminar an attempt is made to understand the mix design of ready mixed concrete, proportioning, physical and chemical properties of materials and influencing factors of mix design used in RMC. Also, and attempt is made to design a software on concrete mix of RMC. In this paper, following points will be covered 1.Physical and chemical properties of materials used in RMC. 2. Influencing factors of mix design. 3. Methods used to design concrete mix of RMC.